The complete mitochondrial genome of ostorhinchus fleurieu (kurtiformes: Apogonidae) and phylogenetic studies of apogoninae - Zhu, Kehua (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of Ostorhinchus fleurieu was first determined, which was 16,521 bp in length, containing 13 protein-coding genes, two rRNA genes, 22 tRNA genes, a putative control region and one origin of replication on the light-strand. The overall base composition included C(29.2%), A(26.7%), T(26.7%) and G(17.4%). Moreover, the 13 PCGs encoded 3800 amino acids in total, twelve of which used the initiation codon ATG except for COI started with GTG. Most of them ended with complete stop codon, whereas three protein-coding genes (COII, ND4 and Cytb) used incomplete stop codon and represented as T. The phylogenetic tree based on the Neighbour Joining method was constructed to provide relationship within Apogoninae, which could be a useful basis for management of this species.